Existence results for doubly nonlinear parabolic equations with two lower order terms and L^1-data - Benkirane, A.; El, Hadfi Y.; El, Moumni M. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.9 We investigate the existence of a renormalized solution for a class of nonlinear parabolic equations with two lower order terms and L^1-data.